The Discourse of Non-Citizens Expulsion Reinvigorated: Examination of Racial Undertones in Asians Expulsion from Uganda in 1972 - Adyanga, Francis A.; Eton, Marus; Ayiga, Natal (African Journal of Social Sciences and Humanities Research, 2021)
The expulsion of non-citizens from countries around the globe is not a new phenomenon. In Africa, there have been numerous documented and undocumented cases after the continent acquired political independence in the 1960’s. In the critical antiracist study, forceful expulsion of citizens of another country may constitute racism. However, our position in this paper is that expulsion of non-citizens for the interest of the host country is not necessarily a racial act. It is on this basis that we examine the expulsion of Asians from Uganda in 1972 and argue that the act, at the basic level of bigotry analysis may not have constituted racism. However, categorizing the Asians population in Uganda by then, the main argument in this paper justifies the expulsion for certain groups on one hand. But on the other hand, we admonish the Uganda government for collective expulsion of the Asians whose ancestors were brought in the country in the late 19th century to build the Uganda railway. Furthermore, the paper argues that as much as many of the Asians were second or third generations having been born in Uganda and were legal citizens, they do not fall within the category of indigenous population. Therefore, their expulsion based on indigeneity and correcting economic imbalance by then is racially unbiased and defensible.
Keywords: Non-citizens; Expulsion; Racism; Legal Citizens